Water quality indexes on aquifer systems from a semi-arid region – a new vulnerability index to sustainable groundwater management - Dhaoui, O. (2022)
Groundwater is an important resource applied for multiple purposes and needs to be protected all over the world. Tunisia is facing the problem of water scarcity due to its arid and semi-arid climate. This region has a rather unstable climate with irregular rainfall quantity and spatial distribution leading to either periods of drought or intensive rainy periods. Groundwater salinization is a major problem associated to natural and anthropogenic processes. The inland aquifer from Menzel Habib (southeastern Tunisia) is exploited for domestic purposes and agricultural activities. Groundwater from Menzel Habib aquifer shows a significant total dissolved solids content (TDS: 1.60-8.71 g/L), associated to the high sodium, chloride, sulfate, magnesium, and calcium water concentrations, and could be used as a water quality indicator. The integration of water contamination indicators and groundwater vulnerability models is a new vision and first-hand information on groundwater quality assessment and sustainable management. The main aim of this study is to assess the vulnerability of the Menzel Habib aquifer using GIS-based vulnerability models to provide information on groundwater contamination and to develop a new index for mapping groundwater vulnerability to salinization. The obtained results indicate different vulnerability degrees, varying from very extremely low to high vulnerability. The highest vulnerability areas are located on the western region, which could be associated to a lower deep of groundwater combined with evaporation processes, and a consequent salinity increase. A modified vulnerability index is proposed by adding to hydrogeological data an eighth parameter, corresponding to TDS water contents. The modified index is based on the standard DRASTIC index and the adding of TDS - DRASTIC_Sal. This new index is a simple approach for aquifer salinization vulnerability assessment, particularly on inland aquifers from arid and semi-arid regions with associated agricultural activities. The expected outcomes of the current study will be a helpful knowledge concerning the status of groundwater vulnerability from Menzel Habib region and will be a decision-making tool to be considered by authorities in land use planning as well as in groundwater resource management.